Experimental investigations of spontaneous damage to wet multi-plate clutches with carbon friction linings Experimentelle Untersuchungen zum Spontanschädigungsverhalten nasslaufender Lamellenkupplungen mit Carbon-Reibbelägen - Groetsch, D.; Stockinger, U.; Schneider, T.; Reiner, F.; Völkel, Katharina; Pflaum, H.; Stahl, K. (Forschung Im Ingenieurwesen-Engineering Research, 2021)
Safety and comfort, while ensuring torque transfer capability, are essential for wet multi-plate clutches. The safety of the torque transmission process largely depends on the endurance of the tribological system against spontaneous and long-term damages. Modern Carbon friction linings in wet multi-plate clutch applications offer superior wear resistance compared to other friction materials, but there is hardly any published data on their spontaneous damage behavior. This article therefore presents results from experimental studies on the spontaneous damage of innovative Carbon friction linings carried out on a component test rig. Furthermore, the influence of different steel plate thicknesses (3.5 mm vs. 6 mm) was investigated. 16 step tests, including visual assessments of the clutches, were performed with Carbon-fiber reinforced plastic (CFRP) and Carbon-fiber reinforced Carbon (C/C) linings in brake operations. The results of the step tests are documented in friction work over friction power diagrams. Results show excellent endurance of modern Carbon friction linings against spontaneous damage and thus makes them suitable for safety relevant high-performance applications. There was no clear influence of the steel plate thickness on spontaneous damage. However, the C/C friction lining ran at a specific energy of up to 5.26 J/mm2 in combination with sliding velocities of up to 67 m/s (high speed application) without failure. This is the highest published spontaneous damage resistance identified for wet clutches.
CRIS-Team Scopus Importer:2025-05-19